Identification of a novel candidate HSD3B2 gene variant for familial hypospadias by whole-exome sequencing - Almaramhy, Hamdi Hameed; Abdul Samad, Firoz; Al-Harbi, Ghadeer; Zaytuni, Dimah; Imam, Syed Nazar; Masoodi, Tariq; Shamsi, Monis Bilal (Frontiers in Genetics, 2023)
Introduction: Hypospadias [MIM: 300633] is one of the most frequent congenital malformations of male external genitalia. The spectrum of genetic variants causing hypospadias is varied, with studies commonly implicating genes critical in fetal steroidogeneic pathway. This is the first genetic study on hypospadias from the Yemen ethnicity and the second to report HSD3B2 mutations in more than one affected individual from the same family. Material and Methods: Surgical hypospadias repair was performed on two hypospadias affected siblings from a consanguineous family. Whole Exome Sequencing (WES) was done to identify the potential pathogenic variant for hypospadias, which was later confirmed by Sanger Sequencing. The identified variant was further analyzed for its pathogenicity by using in silico tools as SIFT, PolyPhen2, Mutation assessor, Mutation Taster, FATHMM and ConSurf. Results: We identified a novel missense mutation (Chr1:119964631T>A,c.507T>A, p.N169K) in 3β- hydroxysteroid 2-dehydrogenase (HSD3B2) gene by WES. Sanger sequencing confirmed that the variant segregated the disease in the family between the affected and non-affected individuals. Both the patients are homozygous, while parents and two unaffected siblings are heterozygous carriers, indicating autosomal recessive pattern of inheritance. The in silico analysis by all the six in silico tools (SIFT, PolyPhen2, Mutation assessor, Mutation Taster, FATHMM and ConSurf) predicted the variant to be pathogenic/deleterious. Discussion: Abnormal fetal steroidogeneic pathway, due to genetic influences may affect the development of male genital tract including the urethral tract closure and morphogenesis of male genitalia. Further, the pathogenicity confirmation of observed variant in this study, by multiple in silico tools characterizes the influence HSD3B2 gene variants may have in the etiology of hypospadias. Conclusion: Understanding of pathogenic manifestation and inheritance of confounding genetic variants in hypospadias is a matter of great concern in particular in familial cases.